Assessing the impact of maladaptive personality traits on driving behaviorativos no comportamento de condução - Montes, Silvana Andrea; Trógolo, Mario A.; Ledesma, Ruben D. (Interação em Psicologia, 2025)
The influence of personality on driver behavior is well-documented in the literature. Previous research in this domain has primarily relied on traditional models, particularly the Big Five. Recently, new personality models have been developed, such as the Alternative Dimensional Model for Personality Disorders (AMPD) proposed in the DSM-V. Despite increasing evidence supporting the utility of AMPD in predicting behavior across various domains, its applicability in predicting driving behaviors remains understudied. This study investigated associations between maladaptive personality traits, based on the AMPD model, and different driving styles, including reckless, aggressive, anxious, dissociative, distress reduction, and careful and patient driving among 1045 drivers from Argentina. The results revealed significant associations between AMPD factors and driving styles across the total sample, as well as in different subgroups based on age and sex. Moreover, multiple linear regression analysis demonstrated that the five AMPD domains (antagonism, disinhibition, detachment, negative affectivity, and psychoticism) differentially predicted each driving style. These findings underline the potential of the AMPD as a valuable framework for enhancing our understanding of drivers’ behaviors, particularly maladaptive driving styles. The implications of these results for driver assessment and the design of road safety interventions are discussed.